CHEMICAL IMPRINTS IN ATMOSPHERIC ABUNDANCES IN PLANET- HOSTING STARS - Mishenina, T.; Basak, N.; Kovtyukh, V. (Одеські астрономічні публікації, 2019)
We examined 12 planet-hosting stars based on homogeneous spectral data (obtained with the SOPHIE echelle spectrograph with R = 75,000 at the OHP, France) and using uniform techniques for determination of parameters and abundances of a series of elements (Li, C, Na, Mg, Al, S, Si, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Ba, La, Ce, Pr, Nd, Sm and Eu). For our set of stars with detected massive planets, we have found [Fe/H] ranging from –0.3 to 0.4 dex. There is the only star for which the lithium content has been reliably shown to be lower than predicted values. Average C/O ratio (0.52±0.08) is slightly lower than the solar one (0.54), and C/O ratios tend to correlate with the planetary mass. Magnesium follows the trend in Galactic chemical evolution exhibiting a dependence on the planetary mass. Manganese and barium are both slightly overabundant.